Komunikasi Organisasi STT Candra Metu dalam Membangun Ikatan Manyama Braya di Banjar Budamanis Sidemen Karangasem - I Kadek Indra; Ulio; Yuliani, Ni Made (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
STT Candra Metu is a youth organization in Budamanis Banjar, Tabola Traditional Village, Sidemen Village, Sidemen District, Karangasem Regency which is engaged in social activities, one of which is building bonds of mutual help between people, namely manyama braya. An organizational communication strategy is urgently needed in building manyama braya ties in Banjar Budamanis so that an active organization is created. This study raises three main issues, namely : What are the forms of manyama braya activities, Organizational Communication Strategies used and what are the implications of STT Candra Metu's Activities in building the manyama braya bond in Banjar Budamanis, Tabola Traditional Village, Sidemen Karangasem? This study uses a qualitative descriptive approach and uses three theories, namely fusion theory, attribution and structural functional theory. Data collection methods used include observation, interviews, documentation and literature. All data is processed using qualitative descriptive techniques. The results of this study indicate that the activities carried out by STT Candra Metu in building the manyama braya bond consist of activities in supporting the implementation of the yadnya ceremony, as a forum for strengthening intimate relationships and channeling creativity, interests and talents. While the communication strategy includes: Vertical communication consisting of bottom-up, top-down and horizontal communication. And the implications of STT Candra Metu in building manyama braya bonds include: Sociol cultural and economic implications for society. Based on this research, it can be concluded that an organizational communication strategy is needed to establish and move the wheels of the organization in building manyama braya ties between fellow STT Candra Metu.